Sonographic and Anthropometric Measurements for Body Composition and Their Relationship with Functioning in Adolescent Obesity - Avar-Aydin, Pinar Ozge; Koyuncu, Esra Gizem; Dogan, Duygu; Ates, Nursena Kologlu; Gurel, Emel; Arda, Nuray; Ozcakar, Levent (Klinische Pädiatrie, 2025)
Obesity is one of the most common chronic diseases seen in children and adolescents. This study aims to examine the impact of obesity on body composition, assessed by sonographic and anthropometric measurements, and health-related quality of life (HRQoL) in adolescents.Anthropometric measurements, sonographic measurements of subcutaneous fat, quadriceps muscle, Achilles tendon thickness, and HRQoL were performed in children between 12–18 years of age. Comparisons between adolescents with obesity and normal body mass index (BMI) were examined.A total of 300 adolescents with similar physical activity levels, 28.7% with obesity, were enrolled. The thickness of mid-forearm/mid-thigh subcutaneous fat tissue and quadriceps muscle was significantly higher in participants with obesity (p≤0.001). Moderate-to-strong correlation with BMI and waist circumference was observed (r>0.40, p<0.01). Participants with longer duration of obesity had thicker quadriceps muscle irrespective of the severity of obesity or presence of metabolic syndrome. Achilles tendon thickness did not differ between the groups. HRQoL was significantly lower in adolescents with obesity and indicated a negative moderate correlation between physical functioning and subcutaneous fat thickness (r<− 0.50, p<0.01).An important relationship between sonographic and anthropometric measurements, and physical functioning was demonstrated in adolescents. Ultrasound seems to have a role in the evaluation of body composition in obesity beyond what is captured by overall BMI. Significantly increased quadriceps muscle thickness in adolescents with obesity, coupled with its relation to the duration of obesity, implies potential temporal association between excess body weight and adaptation of quadriceps muscle.
Keywords: body mass index; health-related quality of life; childhood; obesity; ultrasound; adolescent